Smarter and more connected: Future intelligent transportation system - Sumalee, Agachai; Ho, Hung Wai (My University, 2018)
Emerging technologies toward a connected vehicle-infrastructure-pedestrian environment and big data have made it easier and cheaper to collect, store, analyze, use, and disseminate multi-source data. The connected environment also introduces new approaches to flexible control and management of transportation systems in real time to improve overall system performance. Given the benefits of a connected environment, it is crucial that we understand how the current intelligent transportation system could be adapted to the connected environment.
Keywords: Connected automated vehicles; Connected environment; Cyber-social-physical spaces; Intelligent transportation system; Vehicle-infrastructure-pedestrian